2002
DOI: 10.1038/sj.ejcn.1601282
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-lowering effects of a modified butter-fat: a controlled intervention trial in healthy men

Abstract: Objective: To investigate the lipid-lowering potential of a butter-fat modified through manipulations in bovine feeding to increase the unsaturated : saturated fatty acid ratio. Design: Double-blind, randomised, cross-over intervention trial. Setting: University of Auckland Human Nutrition Unit, New Zealand. Subjects: Twenty healthy, male subjects. Intervention: A residential trial in which all foods and beverages were provided during two intervention periods, comprising 3 weeks of high unsaturated 'modified' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 31 publications
2
68
0
3
Order By: Relevance
“…These combined changes in milk fat composition could, therefore, partially explain the LDLcholesterol reduction observed after the consumption of the L4 diet in comparison with L0 (see Table 4). Our present results are in agreement with the results of Poppitt et al (2002) and Seidel et al (2005). Briefly, Poppitt et al (2002) reported a significant decrease in both total and LDL-cholesterol in plasma from healthy men after consuming a modified butter fat (À5 units of percent total energy intake of SFA and þ 2 units of total energy intake of MUFA) for 3 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…These combined changes in milk fat composition could, therefore, partially explain the LDLcholesterol reduction observed after the consumption of the L4 diet in comparison with L0 (see Table 4). Our present results are in agreement with the results of Poppitt et al (2002) and Seidel et al (2005). Briefly, Poppitt et al (2002) reported a significant decrease in both total and LDL-cholesterol in plasma from healthy men after consuming a modified butter fat (À5 units of percent total energy intake of SFA and þ 2 units of total energy intake of MUFA) for 3 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, a number of intervention studies, which specifically investigated the effects of milk and other dairy fats, did not show significantly increased LDL-cholesterol (91)(92)(93)(94)(95)(96)(97) . Furthermore, there is evidence that fermented milk products are hypocholesterolaemic relative to non-fermented equivalents (93,98) .…”
Section: Dairy Products and Blood Lipidsmentioning
confidence: 99%
“…However, by selecting individuals with highly elevated android body fat, we observed a significant effect of milk on attenuating postprandial hyperglycemia. These results are consistent with the previous observation that the beneficial effects of dairy on metabolic and clinical parameters are more likely to be evident in individuals with elevated risk factors for CVD as there appears to be a distinct “basement effect” associated with dairy intake, in which little to no changes have been observed in healthy individuals with normal or low values (Elwood et al., 2010; Pereira et al., 2002; Poppitt et al., 2002). Therefore, the observed effects can likely be extended to, and perhaps greater in, older obese adults, type 2 diabetes, and those with CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the beneficial effects of dairy on metabolic and clinical parameters are evident in individuals with elevated risk of CVD (Elwood, Pickering, Givens, & Gallacher, 2010; Pereira et al., 2002). However, there appears to be a distinct “floor effect” associated with dairy intake, in which little to no changes were observed in relatively healthy individuals with normal or low baseline levels of cardiovascular risk factors (Poppitt et al., 2002). The complete mechanism underlying the association between dairy intake and cardiometabolic diseases is not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation